MAKING APPLICATION WEBSITE OFFERS AND PROMOTIONS SALES GUITAR USING MACROMEDIA DREAMWEAVER 8.0, MYSQL AND PHP - Bayu Nugroho; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Rapidly evolving information technology today increasingly easy for every person ingetting information. The Internet is a fast and easy way to convey that information toreach the wider community.The use of the website is very useful in efforts to promote offers and inform the shopselling guitars at Guitar Lovers to the consumer. Everything is presented in a webpage display that is easily understood by the consumer, from the main menu to searchuntil guitar specifically according to the brand, type and price of these guitars.Macromedia Dreamweaver 8.0, PHP and MySQL are a few examples of the manysoftware tools that can solve the problem.